Model DL Berbantuan Media AR untuk Meningkatkan Minat dan Hasil Belajar Siswa SD Kota Bengkulu - Aulin, Cindy Rahayu; Supriatna , Irfan (JURIDIKDAS, 2025)
This study aims to analyze the increase in interest and student learning outcomes using the Discovery Learning model assisted by AR (Augmented Reality) media in the thematic learning of class VB SDN 41 Bengkulu City.This research is a Classroom Action Research. The subjects in this study were students of class VB SDN 41 Bengkulu City for the 2022-2023 academic year. The number of students in class VB is 28 students with 13 male students and 15 female students. Data collection techniques using questionnaires, observation, and tests. Research instruments in the form of questionnaire sheets, observation sheets, and test sheets. Data analysis techniques use qualitative and quantitative techniques. The results of the research showed that the percentage value of students' interest in learning cycle I was 59.64%, increased in cycle II by 77.5% and on the average results of the cognitive aspects of student learning in Indonesian language subject cycle I was 74.35 with learning completeness of 75% increasing in cycle II of 80 with learning completeness of 85.71% and science subjects in cycle I of 71.42 with learning completeness of 75% increased in cycle II of 73.92 with learning completeness of 82.14%. Then the average student learning outcomes in the affective aspect of cycle I was 2.615, increasing in cycle II by 2.815 and the average student learning outcomes in the psychomotor aspects of cycle I was 3.00, increasing in cycle II by 3.28. Thus, the use of the Discovery Learning model assisted by AR (Augmented Reality) media can increase student interest and learning outcomes in thematic learning of class VB SDN 41 Bengkulu City.